Odpowiedzi

2010-03-17T20:40:08+01:00
X - bluzka
x+67zł - sukienka
3x = żakiet

x+x+67+3x =532
5x=532-67
5x=465 |:5
x=93 - cena bluzki

93+67=160 - cena sukienki
3*93=279 - cena żakietu
2010-03-17T20:46:36+01:00
Z - bluzka
x - sukienka
y- zakiet

z + x + y = 532
x +67 = z
y= 3z

z + x + y = 532
x= z-67
y= 3z

x+(x+67)+3x=532zł
5x+67=532zł | -67zł
5x+67zł-67zł=532-67zł
5x=465zł | /5
x=93zł

93 - bluzka
160- sukienka
279- zakiet




2010-03-17T20:47:06+01:00
X - cena bluzki
x+67 -cena sukienki
3x -cena żakietu
x+(x+67)+3x=532zł
5x+67=532zł | -67zł
5x+67zł-67zł=532-67zł
5x=465zł | /5
x=93zł

93zł-cena bluzki
93zł+67zł=160zł-cena sukienki
93zł*3=279zł- cena żakietu

Odp: Bluzka kosztowała 93zł, sukienka 160zł, a żakiet 279zł.